Application of Law in Renewable Energy Management and Environmental Legal Issues - Purbo Triwiyoso; Naya Amin Zaini; Irfan Rizky Hutomo (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The development of renewable energy is one of the main solutions to address the energy crisis and environmental problems resulting from the use of fossil fuels. Renewable energy management requires comprehensive regulations to ensure sustainability and environmental protection. In a legal context, the implementation of renewable energy policies in Indonesia faces various challenges, ranging from regulatory aspects, legal certainty and the resulting environmental impacts. Therefore, an in-depth legal study is needed to understand the application of law in renewable energy management and identify related environmental legal issues. This research employs a normative juridical method with a statutory approach and a conceptual approach. The statutory approach tries to analyze legal norms governing renewable energy, including national regulations and international legal instruments that influence energy policy in Indonesia. Meanwhile, the conceptual approach will examine environmental legal principles related to renewable energy management, such as the principle of sustainability, the principle of precaution, and the principle of environmental responsibility. Furthermore, this research also identifies various environmental legal issues arising in renewable energy development, such as licensing and Environmental Impact Analysis (EIA) issues, potential conflicts of interest between renewable energy development and the rights of indigenous communities, and challenges in harmonizing regulations at the national and international levels. Understanding the legal aspects governing renewable energy management and emerging environmental issues is expected to contribute to the development of more effective and sustainable legal policies in the Indonesian energy sector.